Conceptual Approaches to Modeling the Study of the Impact of Digital Employment on Parental Well-being - Natalia TONKIKH; Tatiana MARKOVA; Tatiana KAMAROVA (Communications of International Proceedings, 2022)
The article aims to identify conceptual approaches that can be used to model the study of the impact if digital employment on parental well-being. The authors review multidisciplinary approaches to understanding the concept of well-being and specify the nature of ‘parental well-being’ with the emphasis on its economic and social indicators. In order to achieve these goals, the authors conducted a pilot narrative study (N = 91) among women of childbearing age who received their first experience of remote work during the pandemic. Based on the preliminary analysis of the women’s narratives the authors identified several main tracks in understanding the nature of parental well-being: children's health; children's happiness; mutual understanding and trust; finances, prosperity, well-fed children; time for children. There is proposed a model of eco-environment of parental well-being for the development of methodological support for the study of causal relationships between employment parameters and the level of parental well-being. The authors’ system of metrics has a block structure and comprises objectively measurable (statistical), as well as subjective evaluative (social) metrics. The block model is designed with the aim to study digital employment as a factor influencing the birth rate and parental well-being of citizens raising children under the age of 14. The model is designed to solve the problem of implementing a gender correlation analysis of data in the context of digital employment types.
Keywords: well-being; parental well-being; objectively measurable metrics; subjective evaluative metrics; digital employment; block structure model.